Implementation of Pancasila in Environmental Education (Study at SD Negeri 1 Ungaran) - Wahyuni, Indah Eges (Journal of Creativity Student, 2018)
Environment management principally is the effort to conserve the environment function in which includedpolicy, regulation, utility, maintenance, recovery, controlling and managing of environment. The environment management needed in order in creating sus tainable development that owning an environment perspective for the Indonesia’s humanbeing integral development within faith in God. It’s urgent in understanding in how to applicate or knowing the application aspects of Pancasila values for the environment management to attain a better and useful environment management.